Good With Another Face Or Why The Possessors Of The Trade Marks Let The Counterfeiting Exist? - Зоя Владиславовна Котельникова (Journal of Economic Sociology, 2010)
Production and consumption of the counterfeit products became the world problem today. This increase of economic crime has a lot of reasons. But the more interesting is that the possessors of the trade marks have rather controversial position towards the pirate production and are not always ready to defend their rights actively. We will try to answer this question of why it happens so and we will analyze several types of behavior of the possessors towards counterfeit